Estimation of annual erosion and sedimentation in Babolroud catchment using EPM and Fournier methods - Ehsan Shahiri Tabarestani; Hossein Afzalimehr (تحقیقات کاربردی علوم جغرافیایی)
One of the problems of controlling erosion and sedimentation in catchment areas is the lack of statistical data to accurately estimate the amount of sedimentation and erosion. In order to implement soil protection programs and determine methods to reduce sedimentation, it is necessary to estimate the total volume of annual sediment production. The purpose of this study is to estimate the erosion intensity and sedimentation of Babolroud catchment located in Mazandaran province using EPM and Fournier empirical methods and to determine the accuracy of these models. The results showed that Babolroud catchment is located on the moderate zone of sedimentation and the value of erosion rate is Z = 0.54. Also according to EPM method the sedimentation rate is . The highest amount of erosion is in the northern part of the catchment, which is due to the existence of Non-cultivable land use and erosive soil formations, including alluvial and marsh soils. In order to evaluate the accuracy of the results obtained from the empirical model, the observed information of the two sedimentation stations was used and the results indicate a relative average difference of 23.24% in the EPM model. Also, the results obtained from the Fournier method indicate the inefficiency of this method in estimating the Babolroud catchment due to the lack of consideration of the erosion potential of the area.